Comparison Of Student Learning Outcomes Teached With Information Search And Card Sort Learning Methods - Nisa, Hidayatun; Yahfizham; Siregar, Tanti Jumaisyaroh (Yana Research, 2022)
This study aims to determine the learning outcomes of students who are taught using the information search method, the learning outcomes of students who are taught using the card sort method, and a comparison of the learning outcomes of students who are taught using the information search method and the card sort method in class VII SMP Negeri 13 Medan .This research is a quantitative research, with a quasi-experimental type. The population is all class VII students of SMP Negeri 13 Medan for the 2021/2022 Academic Year which consists of five classes with a total of 160 students. The sample of this research was class VII-1 students who found 30 people as the experimental class 1 which uses the Information Search and VII-2 learning methods which find 30 people as an experimental class 2 which uses the Card Sort learning method. From the average learning outcomes obtained by students who were taught by the card sort information search method better than students who were taught by the card sort method. In the hypothesis test using the t-test with a significant level = 0.05. The price of tcount = 2.25, and ttable = 1.67 thus obtained the price of tcount > ttable or 2.25 <1.67, so that H0 is rejected and H1 is accepted. The conclusions of this study explained that the learning outcomes of class VII students of SMP Negeri 13 Medan on the subject matter of the quadrilaterals taught were significantly different from the method of information retrieval and sorting of cards.